This preview shows page 1. Sign up to view the full content.
Unformatted text preview: indicates an adjoint matrix (transpose plus complex con-jugation). The proof is simpler than the one above. Because the complex conjugate ( ) of a product is the product of the complex conjugates, we can immediately write B A = ( B T ) ( A T ) = ( B T A T ) . (8) Now use the theorem just proven above to rewrite Eq.(8) further as B A = ( B T A T ) = (( AB ) T ) = ( AB ) , (9) which is the desired result. 1...
View Full Document
This note was uploaded on 12/19/2010 for the course PHYSICS ph 409 taught by Professor Wilemski during the Fall '10 term at Missouri S&T.
- Fall '10